Direct Recordings from Human Anterior Insula Reveal its Leading Role within the Error-Monitoring Network. (21st January 2016) - Bastin, Julien; Deman, Pierre; David, Olivier; Gueguen, Maëlle; Benis, Damien; Minotti, Lorella; Hoffman, Dominique; Combrisson, Etienne; Kujala, Jan; Perrone-Bertolotti, Marcela; Kahane, Philippe; Lachaux, Jean-Philippe; et al.
Abstract: The ability to monitor our own errors is mediated by a network that includes dorsomedial prefrontal cortex (dmPFC) and anterior insula (AI). However, the dynamics of the underlying neurophysiological processes remain unclear. In particular, whether AI is on the receiving or driving end of the error-monitoring network is unresolved. Here, we recorded intracerebral electroencephalography signals simultaneously from AI and dmPFC in epileptic patients while they performed a stop-signal task. We found that errors selectively modulated broadband neural activity in human AI. Granger causality estimates revealed that errors were immediately followed by a feedforward influence from AI onto anterior cingulate cortex and, subsequently, onto presupplementary motor area. The reverse pattern of information flow was observed on correct responses. Our findings provide the first direct electrophysiological evidence indicating that the anterior insula rapidly detects and conveys error signals to dmPFC, while the latter might use this input to adapt behavior following inappropriate actions.